2013
DOI: 10.1038/nm.3221
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome-derived IL-1β production induces nitric oxide–mediated resistance to Leishmania

Abstract: Parasites of the Leishmania genus are the causative agents of leishmaniasis in humans, a disease that affects more than 12 million people worldwide. These parasites replicate intracellularly in macrophages, and the primary mechanisms underlying host resistance involve the production of nitric oxide (NO). In this study we show that the Nlrp3 inflammasome is activated in response to Leishmania infection and is important for the restriction of parasite replication both in macrophages and in vivo as demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
338
3
50

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(420 citation statements)
references
References 48 publications
16
338
3
50
Order By: Relevance
“…Interestingly, only live P. brasiliensis efficiently induced the IL-1b release and caspase-1 maturation, indicating that virulence factors are necessary to generate the cellular damage recognized by the NLRs and cause caspase-1 activation. These data are similar to those from several other studies showing that live pathogens are required to activate caspase-1 (34). We then investigated the receptors and inflammasome components involved in P. brasiliensis-mediated caspase-1 activation and showed that Asc inflammasomes were required to promote IL1b induction during P. brasiliensis infection.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, only live P. brasiliensis efficiently induced the IL-1b release and caspase-1 maturation, indicating that virulence factors are necessary to generate the cellular damage recognized by the NLRs and cause caspase-1 activation. These data are similar to those from several other studies showing that live pathogens are required to activate caspase-1 (34). We then investigated the receptors and inflammasome components involved in P. brasiliensis-mediated caspase-1 activation and showed that Asc inflammasomes were required to promote IL1b induction during P. brasiliensis infection.…”
Section: Discussionsupporting
confidence: 86%
“…Both imatinib (i.e. Abl family kinase inhibition alone) and PP2 decreased IL-1β levels, but based on previous studies, this decrease would not be expected to cause healing (Lima-Junior et al, 2013). PP2 also caused lower IFN-γ secretion at high antigenic stimulation (the opposite to what would be expected if the change were contributing to healing in PP2-treated mice; Soong et al, 2012) and decreased IL-17 secretion with Leishmania antigenic stimulation.…”
Section: Sfk and Dual Sfk And Arg Inhibitors Decrease Lesion Size Andmentioning
confidence: 96%
“…PP2 caused decreased secretion of MIP-1α, MIP-2 and CXCL9 (Table S3C), but these changes are not known to decrease BMDMs were incubated with opsonized promastigotes and amastigotes as described in Fig. 1 lesion size (Brandonisio et al, 2002;Lima-Junior et al, 2013;Muller et al, 2003;Oghumu et al, 2010;Ritter and Korner, 2002;Santiago et al, 2004). Given that bosutinib caused a significant inhibition of parasite uptake, and uptake is required for parasite survival, we suspected that the decreased cytokine secretion in bosutinib-treated mice resulted from lower parasite burdens in these mice.…”
Section: Sfk and Dual Sfk And Arg Inhibitors Decrease Lesion Size Andmentioning
confidence: 99%
“…3H). Interestingly, IL-1b was recently demonstrated to be critical for the restriction of Leishmania amazonensis infection (32). Because pyroptosis is required to control the replication of certain intracellular pathogens (33), we quantified this type of cell death in infected macrophages.…”
Section: T Cruzi Triggers Il-1b Productionmentioning
confidence: 99%